Autoimmune/autoinflammatory syndrome induced by adjuvants after multi-component meningococcal serogroup B vaccination in a 7-year-old girl: a case report - Atay, Özge; Asilsoy, Suna; Atakul, Gizem; Al, Serdar; Boyacıoğlu, Özge Kangallı; Çinleti, Tayfun; Uzuner, Nevin; Bozkaya, Özlem Giray; Karaman, Özkan (The Turkish Journal of Pediatrics, 2022)
Background. Vaccines, which make it possible to be protected from many life-threatening infectious diseases, have been used safely and effectively for years. Most vaccines used today contain a variety of adjuvants and exogenous proteins. Severe reactions, in addition to transient and self-limiting mild reactions, mostly caused by these components, have been reported. The effects of vaccine adjuvants on the pathogenesis of immunemediated diseases are still under investigation. The syndrome called Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) has been defined in the literature. Case. We found a novel mutation of autoinflammatory diseases in the genetic analysis of our patient. The patient developed symptoms of prolonged fever, rash, arthritis and serositis after multicomponent serogroup B meningococcal (Bexsero®) vaccination, without a previously known rheumatic disease. In the presence of clinical findings in our patient, the diagnostic criteria of ASIA syndrome were met. Conclusion. To the best of our knowledge, this is the first case report of a patient diagnosed with the autoinflammatory disease with a novel mutation after Bexsero® vaccination. We consider that genetic examinations will be useful in patients with a systemic vaccine reaction in the presence of ASIA when diagnostic criteria are met.